Endoplasmic reticulum targeted cyclometalated iridium(iii) complexes as efficient photodynamic therapy photosensitizers. Issue 19 (17th April 2019) - Yuan, Bo; Liu, Jiangping; Guan, Ruilin; Jin, Chengzhi; Ji, Liangnian; Chao, Hui
Abstract : A series of ER-targeted cyclometalated Ir(iii ) complexes with a gradually extended conjugated area in the main ligand were effective PDT photosensitizers and triggered ER-stress induced apoptosis in cancer cell lines. Abstract : The endoplasmic reticulum (ER) is an indispensable organelle that undertakes the synthesis and export of proteins and membrane lipids. Subtle interferences of the ER redox signaling pathway are very likely to cause ER-stress induced apoptosis. In view of this, we herein present a series of ER-targeted Ir(iii ) complexes (Ir1–Ir3 ) as photodynamic therapy (PDT) photosensitizers with a gradually extended conjugation area in the main ligand, and study the correlation between the conjugation area and PDT performance. The results showed that all of these complexes can accumulate in the ER and effectively induce cell apoptosis after PDT therapeutics (405 nm, 6 J cm −2 ) by an ER stress mechanism, and both their singlet oxygen quantum yields and cytotoxicities increase as the conjugation area extends. All complexes showed PDT efficacy towards different cancer cell lines. Among them, Ir2 exhibited the highest PI value (94.3) against A549 cells with an IC50 down to 0.65 μM. In addition, the post PDT ER-stress induced apoptosis along with the efflux of Ca 2+ from the ER system in A549 cells in a short period of time (45–90 min) with the pretreatment ofIr2 was demonstrated. All of these results indicate the promising potential ofIr2 as an effective PDT photosensitizer.